Analysis on the social psychological mechanism of leaders’ rights from the perspective of legal psychology - Ming Wen (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
In order to better promote the development of society and clarify the influence level of leaders' rights, this paper analyzes the social psychological mechanism of leaders' rights from the perspective of legal psychology. Combined with data analysis method, this paper investigates the influence of leaders' rights. Based on this, the content, method and data quality of leader's right social psychological mechanism are collected and analyzed, and the basic direction that should be followed in the construction of social psychology is to apply it. We should make clear the tool orientation of legal psychology in the construction of social psychology, and vigorously avoid purely data-driven and unrealistic observation orientation, so as to ensure the healthy development of social order.